2013
DOI: 10.1016/j.actbio.2013.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of mouse fibroblasts exposed to a biodegradable iron alloy for stents

Abstract: Iron based materials could constitute an interesting option for cardiovascular biodegradable stent applications due to their superior ductility compared to their counterparts-magnesium alloys. Since the predicted degradation rate of pure iron is considered slow, manganese (35% w/w), an alloying element for iron, was explored to counteract this problem through the powder metallurgy process . However, manganese presents a high cytotoxic potential, thus its effect on cells must first be established. Here, we expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…We recently reported that caveolin-1 expression was decreased in a cultured fibroblastic cell line when exposed to the degradation products of degradable metallic materials (DMMs) [9]. In fact, earlier experiments with 3T3 fibroblast cells showed that cav1 was down-regulated in the presence of DMM and that this pattern of expression was observed as early as 24-hour exposures with Fe-35Mn alloy and was stable up to 48hour exposures.…”
Section: Introductionmentioning
confidence: 98%
“…We recently reported that caveolin-1 expression was decreased in a cultured fibroblastic cell line when exposed to the degradation products of degradable metallic materials (DMMs) [9]. In fact, earlier experiments with 3T3 fibroblast cells showed that cav1 was down-regulated in the presence of DMM and that this pattern of expression was observed as early as 24-hour exposures with Fe-35Mn alloy and was stable up to 48hour exposures.…”
Section: Introductionmentioning
confidence: 98%
“…Fe is an essential nutrient element in the body. From the perspective of corrosion, Fe-based alloys can be used as permanent implants but are not suitable for biodegradable applications due to their low degradation rate. , On the other hand, Mg-based alloys have a very high corrosion rate, which is accompanied by hydrogen gas evolution, pH increase, and premature loss of mechanical integrity. , …”
Section: Introductionmentioning
confidence: 99%
“…Corroded iron degradation products demonstrated no negative cellular reactions in initial in vitro [3][4][5][6][7] and in vivo [8][9][10][11][12][13] studies. However, the focus during most of these investigations was on cardiovascular applications.…”
Section: Introductionmentioning
confidence: 90%